Verbs in “A Fresh N Fruity Spring” Story Book by Lauren Cecil - Hermariyanti Kusumadewi (LPPM Universitas Bina Sarana Informatika, 2022)
English is interesting. In learning English, we start from learning the basic things. A part of Speech is the basic aspect in English. Verbs is parts of speech. By knowing verbs, a person can make simple sentence. It can be used to master vocabulary and to motivate someone to be fluently in English. The title of this research is an analyzing verb in “A Fresh N Fruity Spring” story book by Lauren Cecil. The aim of this research is to find out verbs in a story book, in order to be mastered in vocabulary and making simple sentence from it. The method which will be applied in this research is a descriptive qualitative method. Key words: parts of speech, verb, story book